The Existence of Traditional Food Amidst the Onslaught of Modern Food as a Medium for Local Cultural Literacy (Case Study of Tajin Sobih Sellers) - Ahyana; Romiftahul Ulum (Journal of Practice Learning and Educational Development, 2025)
Businesses worldwide are becoming increasingly competitive, pushing entrepreneurs to innovate, including in the production of traditional foods like Tajin Sobih. This research aims to: (1) analyze how development strategies impact the marketing of Tajin Sobih; and (2) determine how SWAT analysis influences the business development strategy. The research uses a descriptive qualitative approach with data collection methods including interviews, observation, and documentation. The research results indicate that the marketing mix is the main strategy for developing the Tajin Sobih business. This strategy includes increased promotion, packaging innovation, and distribution expansion. SWAT analysis places this business as having significant strengths and opportunities to remain viable. The main strengths are the distinctive taste, local customer loyalty, and the cultural value inherent in the product as part of the region's culinary identity. The opportunity comes from the increasing interest in traditional food and public awareness of the importance of Local Cultural Literacy, which is understanding and appreciating local cultural heritage. Challenges such as limited digital promotion and brand awareness still restrict sales of Tajin Sobih. Therefore, development strategies need to be directed toward strengthening branding based on local cultural literacy, sustainable innovation, and adaptation to the modern market so that Tajin Sobih remains competitive and continues to grow.